2021
DOI: 10.1021/acs.energyfuels.1c03409
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure Transformations in Kerogen from Longmaxi Shales in Response to Tectonic Stress as Investigated by HRTEM, FTIR, and 13C NMR

Abstract: Kerogen molecular structure controls the micropore (<2 nm diameter) evolution in shale and exerts a significant impact on shale gas adsorption, desorption, and diffusion. However, the influence of tectonic deformation on kerogen structure and organic micropores needs intensive study. Our study mainly focuses on the transformations in the extracted kerogen structure and organic micropores of Longmaxi shale during tectonic deformation. Vitrinite reflectance measurement (VRM) and Raman spectroscopy (RS) were util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…These bands were also observed in the FTIR spectra of coals (Coates, 2000;Van Niekerk et al, 2008;Okolo et al, 2015;Phan et al, 2021;. The band at 1,030 cm −1 observed in Figure 5 indicates the intensity of C-C stretching vibrations within an aliphatic skeleton (Okolo et al, 2015;Jing et al, 2019;Razavian and Fatemi, 2021;Shang et al, 2021). The 1,280-1,000 cm −1 peak heights of all pyrolyzed samples showed a steady increase with increasing VR, and the narrowing peak width as VR increased indicated that some organic functional groups (such as C-O and O-H) were rapidly pyrolyzed and hence sharply decreased; the remaining functional groups (such as C-C) were slowly pyrolyzed and hence showed less of a decrease.…”
Section: Ftirmentioning
confidence: 70%
See 1 more Smart Citation
“…These bands were also observed in the FTIR spectra of coals (Coates, 2000;Van Niekerk et al, 2008;Okolo et al, 2015;Phan et al, 2021;. The band at 1,030 cm −1 observed in Figure 5 indicates the intensity of C-C stretching vibrations within an aliphatic skeleton (Okolo et al, 2015;Jing et al, 2019;Razavian and Fatemi, 2021;Shang et al, 2021). The 1,280-1,000 cm −1 peak heights of all pyrolyzed samples showed a steady increase with increasing VR, and the narrowing peak width as VR increased indicated that some organic functional groups (such as C-O and O-H) were rapidly pyrolyzed and hence sharply decreased; the remaining functional groups (such as C-C) were slowly pyrolyzed and hence showed less of a decrease.…”
Section: Ftirmentioning
confidence: 70%
“…The out-of-plane aromatic C-H bending vibrations indicated the presence of substituted aromatic species in aromatic rings; and trans-and cis-CH 2 in long, saturated aromatic CH-CH chains were observed in the 900-700 cm −1 region of the spectra in the entirely pyrolyzed samples (Coates, 2000;Van Niekerk et al, 2008;Malumbazo et al, 2011;Okolo et al, 2015;Jing et al, 2019;Shang et al, 2021;. The peaks in the 900-700 cm −1 region of the spectra became more obvious with increasing VR (Figure 5), indicating an increase in aromatic groups.…”
Section: Ftirmentioning
confidence: 99%
“…The source rock reached the generation peak of gaseous hydrocarbon and formed a great amount of expansion micropores in organic matter. 38,39 Xie et al , Li et al , and Wang et al also suggested that micropores are the main contributor to the specific surface area in over mature shale gas reservoirs, even with a ratio higher than 90%. Therefore, the micropore filling theory can better characterize the adsorption behavior of CO 2 in shale.…”
Section: Resultsmentioning
confidence: 99%
“…23−26 Moreover, HRTEM can also visualize the quantitative structural parameters of aromatic lamellae to support the molecular structure characterization results. 27 In addition to the above individual experimental analyses, some scholars have established an average molecular 2D structural model for kerogen based on kerogen elemental analysis and molecular structure characterization experimental data. 28,29 With the development of computer technology, several novel means of molecular structure simulation have emerged.…”
Section: Introductionmentioning
confidence: 99%